Repeated turnovers in Late Jurassic faunal assemblages of the Gulf of Mexico: correlation with cold ocean water - Zell, Patrick; Stinnesbeck, Wolfgang; Brysch, Sven; Schorndorf, Nils (Journal of South American earth sciences, 2019)
Our research on Late Jurassic-earliest Cretaceous (Kimmeridgian-earliest Berriasian) marine shelf to bathyal sediments in northeastern Mexico reveals significant repeated oceanic and biotic turnovers in the northwestern Proto-Gulf of Mexico. We here document these environmental changes based on alternating cold and warm water mollusk assemblages, element concentrations and organofacies, as well as associated changes in sea level. We hypothesize that oscillations in the oceanic current system of the Gulf of Mexico were responsible for appearance of cold-water assemblages of Boreal and possibly Austral origins, situated in specific horizons which were previously described as poor in fossil content or even as fossil-free. In addition, these specific horizons show significant changes in element concentrations and organofacies and correlate to relative sea-level changes.